A kind of dry-mixed high-strength fine stone concrete and its preparation process
Through the mixing process of ready-mixed additives with silicate cement, fine stone and sand, the problems of poor fluidity and low early strength of fine stone concrete are solved, and dry-mixed high-strength fine stone concrete with high strength, slightly expanded and good durability performance are achieved.
Patent Information
- Application Number
- CN202411011543.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-07-26
AI Technical Summary
The existing fine stone concrete has problems such as poor fluidity, low early strength, poor slump retention, and lack of construction, especially after transportation and delivery to the construction site, the liquidity loss and ease of ease becomes worse.
Premixed admixture is obtained by premixing ore powder, silica fume, fly ash, modified water reducing agent, defoaming agent, expansion agent and premature strength agent, and the silicate cement, fine stone and sand are stirred and the premixed admixture is added to prepare dry-mixed high-strength fine stone concrete.
The pre-strength and high-strength, slightly expanded and shrink-free, good durability and fatigue resistance of fine stone concrete are achieved, and the problems of fluidity loss and erroneous deterioration are avoided. The finished products are prefabricated and packaged in the factory, and the ratio is controllable.
Smart Images

Figure BDA0004964520470000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to dry-mixed high-strength fine stone concrete and a preparation process thereof. Background Art
[0002] Fine aggregate concrete generally refers to concrete with a maximum particle size of coarse aggregate not exceeding 15mm. Its performance is affected by many factors, including the selection of raw materials for fine aggregate concrete (including the type of inorganic coarse aggregate, the performance of water reducing agent, etc.), mix ratio, and process. Conventional fine aggregate concrete generally has the characteristics of poor fluidity, low early strength, poor collapse resistance, and lack of construction performance. Moreover, after the materials are mixed and stirred, the initial fluidity is acceptable, but after being transported to the construction site, the fluidity is lost and the workability deteriorates. Therefore, it is urgent to develop a dry-mixed high-strength fine aggregate concrete with higher construction performance to solve the above problems. Summary of the invention
[0003] The object of the present invention is to provide a dry-mixed high-strength fine-stone concrete and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a dry-mixed high-strength fine stone concrete and a preparation process thereof, comprising the following steps:
[0005] The mineral powder, silica fume, fly ash, modified water reducing agent, defoamer, expansion agent and early strength agent are pre-mixed to obtain a premixed admixture; then silicate cement, fine stone and sand are put into a mixer and stirred for 60 to 90 seconds; finally, the previously prepared premixed admixture is put into the mixer and stirred for 3 to 5 minutes, and the dry-mixed high-strength fine stone concrete is packaged; wherein the preparation method of the modified water reducing agent comprises the following steps:
[0006] Step 1:
[0007] After 3,4-dihydroxyphenylacetic acid is melted at 130-135°C, methyl allyl polyoxyethylene ether is added while maintaining the temperature, and p-toluenesulfonic acid is added as a catalyst. During the reaction, nitrogen is continuously introduced to remove the generated water vapor, and the reaction is carried out for 6-8 hours to obtain an esterification intermediate.
[0008] Step 2:
[0009] Under nitrogen protection, undecylenic acid and toluene are mixed, heated to 75-85°C, Karstedt catalyst is added, and chlorodimethylsilane is added dropwise. After the addition is complete, the mixture is kept warm for 3-5 hours, and the toluene is removed by rotary evaporation to obtain a chlorocarboxyl silane monomer.
[0010] Step 3:
[0011] The esterification intermediate and the chlorine-containing carboxyl silane monomer are mixed, and a phase transfer catalyst, benzyltriethylammonium chloride, is added, and heated to 80-90°C under nitrogen protection, and stirred for reaction for 2-3 hours. After natural cooling, a sodium hydroxide solution is added to adjust the pH to 6-7, and the reaction is carried out for 2-3 hours. Saturated sodium chloride is added for washing, and the mixture is dried to obtain a dicarboxyl silane monomer;
[0012] Step 4:
[0013] Disperse dicarboxyl silane monomer in water, heat the oil bath to 75-85°C, add acrylic acid and sodium methacrylic acid with stirring, use ammonium persulfate as initiator, keep warm for 2-3 hours, cool naturally after the reaction, then add NaOH solution to adjust the pH to 6-7 to obtain a modified water reducer.
[0014] Furthermore, the amount of each component, by weight, is 10-20 parts of mineral powder, 10-20 parts of silica fume, 10-20 parts of fly ash, 2-4 parts of modified water reducing agent, 0.5-1 part of defoaming agent, 0.2-0.3 part of expansion agent, 5-10 parts of early strength agent, 460-500 parts of silicate cement, 250-300 parts of fine stone, and 150-180 parts of sand.
[0015] Furthermore, the fine stone is granite with a particle size of 5 to 12 mm; the sand particle size is 0 to 4.7 mm; the mineral powder particle size is 300 to 400 meshes; the silica fume particle size is 350 to 400 meshes; and the fly ash particle size is 200 to 300 meshes.
[0016] Furthermore, in step 1, the molecular weight of methyl allyl polyoxyethylene ether is 2400-3000.
[0017] Furthermore, in step 1, the molar ratio of 3,4-dihydroxyphenylacetic acid to methyl allyl polyoxyethylene ether is (2.5-3):1.
[0018] Furthermore, in step 2, the molar ratio of undecylenic acid to chlorodimethylsilane is 1:1.
[0019] Furthermore, in step 3, the esterification intermediate and the chlorine-containing carboxyl silane monomer are mixed in a molar ratio of phenolic hydroxyl group to chlorine group of 1:1.
[0020] Furthermore, in step 4, the weight ratio of dicarboxyl silane monomer, acrylic acid, and sodium methacrylic acid sulfonate is (2-2.4):(18-20):1.
[0021] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention mixes mineral powder, silica fume, fly ash, modified water reducing agent, defoamer, expansion agent, and early strength agent to obtain a premixed admixture; then, after mixing silicate cement, fine stone, and sand, the premixed admixture is added to obtain dry-mixed high-strength fine stone concrete. The fine stone concrete prepared by the present invention is a factory-prefabricated packaged finished product, the proportion of raw materials is precisely controllable, and water is added on-site to stir and form, which avoids the poor fluidity loss of fine stone concrete, and has the characteristics of early strength, high strength, slight expansion without shrinkage, good durability and fatigue resistance. The present invention makes fine stone from high-quality granite, which is washed, dried and dust-removed for standby use, and sand, mineral powder, silica powder, and fly ash are added to increase workability and compactness to prevent segregation; then expansion agent, defoamer, and water reducing agent are added to make it have greater compressive strength after maintenance.
[0022] During use, polycarboxylic acid is adsorbed on the surface of cement particles to produce a steric hindrance effect, which has a crucial impact on the dispersibility of the cement system; generally, increasing the length of the side chain of the polycarboxylic acid molecule can increase the thickness of the adsorption layer, so a straight-chain macromolecular monomer is used as a raw material to prepare polycarboxylic acid. When the molecular weight of the straight-chain macromolecular monomer is less than 2400, the polycarboxylic acid side chain obtained by polymerization is in a good extension state, and increasing the length of the side chain can effectively increase the thickness of the adsorption layer on the surface of the cement particles; when the molecular weight of the straight-chain macromolecular monomer reaches 2400, the length of the side chain continues to increase, and the side chain ends will be entangled together, resulting in that as the molecular weight of the straight-chain macromolecular monomer increases, the thickness of the adsorption layer will not increase significantly due to the increase in molecular weight, so the molecular weight of the ordinary polycarboxylic acid side chain is generally 2400. In the present invention, the modified water reducer is obtained by the polymerization reaction of a macromolecular monomer dicarboxyl silane monomer and a small molecular monomer acrylic acid and sodium methacrylic acid sulfonate, wherein the dicarboxyl silane monomer is a Y-shaped macromolecular monomer, which can effectively increase the steric hindrance of the polycarboxylic acid side chain, increase the thickness of the adsorption layer on the surface of the cement particles, and thus improve the dispersibility. The dicarboxyl silane monomer contains silicone and long carbon chains, and has good hydrophobic properties. It also contains two carboxyl groups at the end of its molecular chain. The carboxyl groups on the side chains form electrostatic repulsion with the carboxyl groups on the main chain, which can keep the long side chains in a stretched state, forming a greater steric hindrance and increasing the dispersibility of cement particles. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Materials and sources used in the present invention: methyl allyl polyoxyethylene ether has a molecular weight of 2400 and comes from Hubei Longxin Chemical Industry Co., Ltd.; mineral powder is S95 mineral powder, which comes from Shandong Kefa Building Materials Co., Ltd.; silica fume comes from Sichuan Awende New Materials Co., Ltd., with a product number of 960U and a particle size of 350-400 meshes; fly ash is first-class fly ash, which comes from Jining Hengzhi New Building Materials Co., Ltd., with a particle size of 200-300 meshes; defoamer comes from Yantai Hengxin Chemical Technology Co., Ltd., with a product number of THIX-288; expansion agent is a magnesium oxide expansion agent with a magnesium oxide content of more than 30%, which comes from Hefei Sanyuan Special Building Materials Factory; early strength agent is calcium formate, which comes from Wujiang Minghao Chemical Co., Ltd.; silicate cement has a strength of PO42.5 and comes from Shandong Xingde Geotechnical Materials Co., Ltd.; fine stone is granite, which comes from Lingshou County Jinyi Mineral Products Trading Co., Ltd., with a particle size of 5-12 mm; sand is river sand, which comes from Guizhou Zhongsha Building Materials Co., Ltd., with a particle size of 1-3 mm.
[0025] Embodiment 1: A dry-mixed high-strength fine stone concrete and a preparation process thereof, comprising the following steps:
[0026] 20kg of mineral powder, 20kg of silica fume, 20kg of fly ash, 2kg of modified water reducing agent, 0.5kg of defoaming agent, 0.2kg of expansion agent, and 6kg of early strength agent are pre-mixed to obtain a premixed admixture; 460kg of silicate cement, 250kg of fine stone, and 180kg of sand are added to a mixer and stirred for 60s; finally, the previously prepared premixed admixture is added and stirred for 3min, and packaged to obtain dry-mixed high-strength fine stone concrete; wherein the preparation method of the modified water reducing agent comprises the following steps:
[0027] Step 1:
[0028] After 3,4-dihydroxyphenylacetic acid is melted at 130°C, methyl allyl polyoxyethylene ether is added under heat preservation, and p-toluenesulfonic acid is added as a catalyst. During the reaction, nitrogen is continuously introduced to remove the generated water vapor, and the reaction is carried out for 6 hours to obtain an esterification intermediate; wherein the molar ratio of 3,4-dihydroxyphenylacetic acid to methyl allyl polyoxyethylene ether is 2.5:1, and the amount of p-toluenesulfonic acid is 2% of the total weight of the reactants;
[0029] Step 2:
[0030] Under nitrogen protection, undecylenic acid and toluene are mixed, heated to 75°C, Karstedt catalyst is added, and chlorodimethylsilane is added dropwise. After the addition is completed, the mixture is kept warm for 3 hours, and the toluene is removed by rotary evaporation to obtain chlorocarboxyl silane; wherein the molar ratio of undecylenic acid to chlorodimethylsilane is 1:1;
[0031] Step 3:
[0032] The esterification intermediate and the chlorine-containing carboxyl silane are mixed in a molar ratio of phenolic hydroxyl group to chlorine group of 1:1, and a phase transfer catalyst, benzyltriethylammonium chloride, is added, and heated to 80°C under nitrogen protection, and stirred for reaction for 2 hours. After natural cooling, a sodium hydroxide solution with a mass fraction of 40wt.% is added to adjust the pH to 7, and the reaction is carried out for 2 hours. Saturated sodium chloride is added for washing and drying to obtain a dicarboxyl silane monomer; the molar ratio of chlorine group to phenolic hydroxyl group is 1:1;
[0033] Step 4:
[0034] Disperse dicarboxyl silane monomer in water, heat the oil bath to 75°C; add acrylic acid and sodium methacrylate sulfonate with stirring, use ammonium persulfate as initiator (the dosage is 2% of the total weight of the monomers), continue to keep warm for 2 hours, cool naturally after the reaction is completed, and then add 30wt.% NaOH solution to adjust the pH to 7 to obtain a modified water reducer; wherein the weight ratio of dicarboxyl silane monomer, acrylic acid and sodium methacrylate sulfonate is 2:20:1.
[0035] Embodiment 2: A dry-mixed high-strength fine stone concrete and a preparation process thereof, comprising the following steps:
[0036] 16kg of mineral powder, 18kg of silica fume, 16kg of fly ash, 2.2kg of modified water reducing agent, 0.7kg of defoaming agent, 0.21kg of expansion agent, and 6.8kg of early strength agent are pre-mixed to obtain a premixed admixture; 470kg of silicate cement, 275kg of fine stone, and 166kg of sand are added to a mixer and stirred for 75s; finally, the previously prepared premixed admixture is added and stirred for 4min, and packaged to obtain dry-mixed high-strength fine stone concrete; wherein the preparation method of the modified water reducing agent comprises the following steps:
[0037] Step 1:
[0038] After 3,4-dihydroxyphenylacetic acid is melted at 135°C, methyl allyl polyoxyethylene ether is added under heat preservation, and p-toluenesulfonic acid is added as a catalyst. During the reaction, nitrogen is continuously introduced to remove the generated water vapor. The reaction is carried out for 7 hours to obtain an esterification intermediate; wherein the molar ratio of 3,4-dihydroxyphenylacetic acid to methyl allyl polyoxyethylene ether is 2.5:1, and the amount of p-toluenesulfonic acid is 2% of the total weight of the reactants;
[0039] Step 2:
[0040] Under nitrogen protection, undecylenic acid and toluene are mixed, heated to 80°C, Karstedt catalyst is added, and chlorodimethylsilane is added dropwise. After the addition is completed, the mixture is kept warm for 4 hours, and the toluene is removed by rotary evaporation to obtain chlorocarboxysilane; wherein the molar ratio of undecylenic acid to chlorodimethylsilane is 1:1;
[0041] Step 3:
[0042] The esterification intermediate and the chlorine-containing carboxyl silane are mixed in a molar ratio of phenolic hydroxyl group to chlorine group of 1:1, and a phase transfer catalyst, benzyltriethylammonium chloride, is added, and heated to 85°C under nitrogen protection, and stirred for reaction for 2.5 hours. After natural cooling, a sodium hydroxide solution with a mass fraction of 40wt.% is added to adjust the pH to 7, and the reaction is carried out for 2.5 hours. Saturated sodium chloride is added for washing and drying to obtain a dicarboxyl silane monomer; the molar ratio of chlorine group to phenolic hydroxyl group is 1:1;
[0043] Step 4:
[0044] Disperse dicarboxyl silane monomer in water, heat the oil bath to 80°C; add acrylic acid and sodium methacrylate sulfonate with stirring, use ammonium persulfate as an initiator (the amount is 2% of the total weight of the monomers), continue to keep warm for 2.5 hours, cool naturally after the reaction is completed, and then add 30wt.% NaOH solution to adjust the pH to 7 to obtain a modified water reducer; wherein the weight ratio of dicarboxyl silane monomer, acrylic acid and sodium methacrylate sulfonate is 2:20:1.
[0045] Embodiment 3: A dry-mixed high-strength fine stone concrete and a preparation process thereof, comprising the following steps:
[0046] 14kg of mineral powder, 15kg of silica fume, 16kg of fly ash, 2.4kg of modified water reducing agent, 0.8kg of defoaming agent, 0.22kg of expansion agent, and 8.2kg of early strength agent are pre-mixed to obtain a premixed admixture; 480kg of silicate cement, 285kg of fine stone, and 155kg of sand are added to a mixer and stirred for 90s; finally, the previously prepared premixed admixture is added and stirred for 5min, and packaged to obtain dry-mixed high-strength fine stone concrete; wherein the preparation method of the modified water reducing agent comprises the following steps:
[0047] Step 1:
[0048] After 3,4-dihydroxyphenylacetic acid is melted at 130°C, methyl allyl polyoxyethylene ether is added while keeping the temperature, p-toluenesulfonic acid is added as a catalyst, nitrogen is continuously introduced during the reaction to remove the generated water vapor, and the reaction is carried out for 8 hours to obtain an esterification intermediate; wherein the molar ratio of 3,4-dihydroxyphenylacetic acid to methyl allyl polyoxyethylene ether is 2.5:1, and the amount of p-toluenesulfonic acid is 2% of the total weight of the reactants;
[0049] Step 2:
[0050] Under nitrogen protection, undecylenic acid and toluene are mixed, heated to 85°C, Karstedt catalyst is added, and chlorodimethylsilane is added dropwise. After the addition is completed, the mixture is kept warm for 5 hours, and the toluene is removed by rotary evaporation to obtain chlorocarboxyl silane; wherein the molar ratio of undecylenic acid to chlorodimethylsilane is 1:1;
[0051] Step 3:
[0052] The esterification intermediate and the chlorine-containing carboxyl silane are mixed in a molar ratio of phenolic hydroxyl group to chlorine group of 1:1, and a phase transfer catalyst, benzyltriethylammonium chloride, is added, and heated to 90°C under nitrogen protection, and stirred for reaction for 3 hours. After natural cooling, a sodium hydroxide solution with a mass fraction of 40wt.% is added to adjust the pH to 7, and the reaction is carried out for 3 hours. Saturated sodium chloride is added for washing and drying to obtain a dicarboxyl silane monomer; the molar ratio of chlorine group to phenolic hydroxyl group is 1:1;
[0053] Step 4:
[0054] Disperse dicarboxyl silane monomer in water, and heat the oil bath to 85°C; add acrylic acid and sodium methacrylate sulfonate with stirring, and use ammonium persulfate as an initiator (the amount used is 2% of the total weight of the monomers), and continue to keep warm for 3 hours. After the reaction is completed, cool naturally, and then add 30wt.% NaOH solution to adjust the pH to 7 to obtain a modified water reducer; wherein the weight ratio of dicarboxyl silane monomer, acrylic acid, and sodium methacrylate sulfonate is 2:20:1.
[0055] Embodiment 4: A dry-mixed high-strength fine stone concrete and a preparation process thereof, comprising the following steps:
[0056] 12kg of mineral powder, 14kg of silica fume, 12kg of fly ash, 2.8kg of modified water reducing agent, 0.89kg of defoaming agent, 0.23kg of expansion agent, and 10kg of early strength agent are pre-mixed to obtain a premixed admixture; 490kg of silicate cement, 300kg of fine stone, and 150kg of sand are added to a mixer and stirred for 90s; finally, the previously prepared premixed admixture is added and stirred for 5min, and packaged to obtain dry-mixed high-strength fine stone concrete; wherein the preparation method of the modified water reducing agent comprises the following steps:
[0057] Step 1:
[0058] After 3,4-dihydroxyphenylacetic acid is melted at 135°C, methyl allyl polyoxyethylene ether is added while keeping warm, p-toluenesulfonic acid is added as a catalyst, nitrogen is continuously introduced during the reaction to remove the generated water vapor, and the reaction is carried out for 8 hours to obtain an esterification intermediate; wherein the molar ratio of 3,4-dihydroxyphenylacetic acid to methyl allyl polyoxyethylene ether is 2.5:1, and the amount of p-toluenesulfonic acid is 2% of the total weight of the reactants;
[0059] Step 2:
[0060] Under nitrogen protection, undecylenic acid and toluene are mixed, heated to 85°C, Karstedt catalyst is added, and chlorodimethylsilane is added dropwise. After the addition is completed, the mixture is kept warm for 5 hours, and the toluene is removed by rotary evaporation to obtain chlorocarboxyl silane; wherein the molar ratio of undecylenic acid to chlorodimethylsilane is 1:1;
[0061] Step 3:
[0062] The esterification intermediate and the chlorine-containing carboxyl silane are mixed in a molar ratio of phenolic hydroxyl group to chlorine group of 1:1, and a phase transfer catalyst, benzyltriethylammonium chloride, is added, and heated to 90°C under nitrogen protection, and stirred for reaction for 3 hours. After natural cooling, a sodium hydroxide solution with a mass fraction of 40wt.% is added to adjust the pH to 7, and the reaction is carried out for 3 hours. Saturated sodium chloride is added for washing and drying to obtain a dicarboxyl silane monomer; the molar ratio of chlorine group to phenolic hydroxyl group is 1:1;
[0063] Step 4:
[0064] Disperse dicarboxyl silane monomer in water, and heat the oil bath to 85°C; add acrylic acid and sodium methacrylate sulfonate with stirring, and use ammonium persulfate as an initiator (the amount used is 2% of the total weight of the monomers), and continue to keep warm for 3 hours. After the reaction is completed, cool naturally, and then add 30wt.% NaOH solution to adjust the pH to 7 to obtain a modified water reducer; wherein the weight ratio of dicarboxyl silane monomer, acrylic acid, and sodium methacrylate sulfonate is 2:20:1.
[0065] Comparative Example 1: Methyl allyl polyoxyethylene ether was directly used as the macromonomer to prepare the water reducer, and the other parameters were the same as those in Example 1.
[0066] 20kg of mineral powder, 20kg of silica fume, 20kg of fly ash, 2kg of water reducing agent, 0.5kg of defoaming agent, 0.2kg of expansion agent and 6kg of early strength agent were pre-mixed to obtain a premixed admixture; 460kg of silicate cement, 250kg of fine stone and 180kg of sand were put into a mixer and stirred for 60s; finally, the previously prepared premixed admixture was put into the mixer and stirred for 3min, and the dry-mixed high-strength fine stone concrete was packaged, wherein the preparation method of the water reducing agent is as follows: methyl allyl polyoxyethylene ether is dispersed in water, and the oil bath is heated to 75°C; acrylic acid and sodium methyl propylene sulfonate are added with stirring, and ammonium persulfate is used as an initiator (the amount is 2% of the total weight of the monomer), and the temperature is kept warm for 2h. After the reaction is completed, the mixture is naturally cooled, and then a 30wt.% NaOH solution is added to adjust the pH to 7 to obtain a modified water reducing agent; wherein the weight ratio of methyl allyl polyoxyethylene ether, acrylic acid and sodium methyl propylene sulfonate is 2:20:1.
[0067] Comparative Example 2: p-Hydroxyphenylacetic acid was used instead of 3,4-dihydroxyphenylacetic acid, and the other parameters were the same as those in Example 2.
[0068] 16kg of mineral powder, 18kg of silica fume, 16kg of fly ash, 2.2kg of modified water reducing agent, 0.7kg of defoaming agent, 0.21kg of expansion agent, and 6.8kg of early strength agent are pre-mixed to obtain a premixed admixture; 470kg of silicate cement, 275kg of fine stone, and 166kg of sand are added to a mixer and stirred for 75s; finally, the previously prepared premixed admixture is added and stirred for 4min, and packaged to obtain dry-mixed high-strength fine stone concrete; wherein the preparation method of the modified water reducing agent comprises the following steps:
[0069] Step 1:
[0070] After para-hydroxyphenylacetic acid is melted at 135° C., methyl allyl polyoxyethylene ether is added while keeping the temperature, and p-toluenesulfonic acid is added as a catalyst. During the reaction, nitrogen is continuously introduced to remove the generated water vapor. The reaction is carried out for 7 hours to obtain an esterification intermediate; wherein the molar ratio of p-hydroxyphenylacetic acid to methyl allyl polyoxyethylene ether is 2.5:1, and the amount of p-toluenesulfonic acid is 2% of the total weight of the reactants;
[0071] Step 2:
[0072] Under nitrogen protection, undecylenic acid and toluene are mixed, heated to 80°C, Karstedt catalyst is added, and chlorodimethylsilane is added dropwise. After the addition is completed, the mixture is kept warm for 4 hours, and the toluene is removed by rotary evaporation to obtain chlorocarboxysilane; wherein the molar ratio of undecylenic acid to chlorodimethylsilane is 1:1;
[0073] Step 3:
[0074] The esterification intermediate and the chlorine-containing carboxyl silane are mixed in a molar ratio of phenolic hydroxyl group to chlorine group of 1:1, and a phase transfer catalyst, benzyltriethylammonium chloride, is added, and heated to 85°C under nitrogen protection, and stirred for reaction for 2.5 hours. After natural cooling, a sodium hydroxide solution with a mass fraction of 40wt.% is added to adjust the pH to 7, and the reaction is carried out for 2.5 hours. Saturated sodium chloride is added for washing and drying to obtain a carboxyl silane monomer; the molar ratio of chlorine group to phenolic hydroxyl group is 1:1;
[0075] Step 4:
[0076] Disperse carboxyl silane monomer in water, heat the oil bath to 80°C; add acrylic acid and sodium methacrylate sulfonate with stirring, use ammonium persulfate as initiator (the dosage is 2% of the total weight of the monomers), continue to keep warm for 2.5 hours, cool naturally after the reaction is completed, and then add 30wt.% NaOH solution to adjust the pH to 7 to obtain a modified water reducer; wherein the weight ratio of carboxyl silane monomer, acrylic acid and sodium methacrylate sulfonate is 2:20:1.
[0077] Experiment: The fine stone concrete prepared in Examples 1 to 4 and Comparative Examples 1 to 2 was mixed with admixture water to test its physical and mechanical properties. The experimental results are shown in the following table. Among them, the fluidity was tested according to the truncated cone fluidity test, and the test was carried out with reference to the standard GB / T 50448-2015; the compressive strength test method was to make the fine stone concrete into a 150mm×150mm×150mm specimen, and cure it for 1, 3, and 28 days at 20°C and a relative humidity of 85%, and test it with reference to GB / T 50081-2019; the vertical expansion rate was tested using a vertical expansion rate meter; the water consumption was the percentage of the added admixture water in the total weight of the fine stone concrete.
[0078]
[0079] Conclusion: The data of Examples 1 to 4 and Comparative Examples 1 to 2 show that the fine stone concrete prepared by the present invention has good performance. The data of Example 1 and Comparative Example 1 show that compared with the ordinary water reducer, the modified water reducer prepared by adding the present invention has good performance, and the mechanical strength of the material after curing is higher. The data of Example 2 and Comparative Example 2 show that the use of 3,4-dihydroxyphenylacetic acid can prepare a Y-shaped dicarboxyl silane monomer, and the water reducer obtained after polymerization with a small molecule monomer has better performance.
[0080] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing dry-mixed high-strength fine-stone concrete, characterized in that: The following steps are involved: Premix mineral powder, silica fume, fly ash, modified water reducing agent, defoamer, expansion agent and early strength agent to obtain a premixed admixture; then put silicate cement, fine stone and sand into a mixer and stir for 60 to 90 seconds; finally, put the previously prepared premixed admixture into the mixer and stir for 3 to 5 minutes, and pack it to obtain dry-mixed high-strength fine stone concrete; The preparation method of the modified water reducing agent comprises the following steps: Step 1: After 3,4-dihydroxyphenylacetic acid is melted at 130-135°C, methyl allyl polyoxyethylene ether is added while maintaining the temperature, and p-toluenesulfonic acid is added as a catalyst. During the reaction, nitrogen is continuously introduced to remove the generated water vapor, and the reaction is carried out for 6-8 hours to obtain an esterification intermediate. Step 2: Under nitrogen protection, undecylenic acid and toluene are mixed, heated to 75-85°C, Karstedt catalyst is added, and chlorodimethylsilane is added dropwise. After the addition is complete, the mixture is kept warm for 3-5 hours, and the toluene is removed by rotary evaporation to obtain a chlorocarboxyl silane monomer. Step 3: The esterification intermediate and the chlorine-containing carboxyl silane monomer are mixed, and a phase transfer catalyst, benzyltriethylammonium chloride, is added, and heated to 80-90°C under nitrogen protection, and stirred for reaction for 2-3 hours. After natural cooling, a sodium hydroxide solution is added to adjust the pH to 6-7, and the reaction is carried out for 2-3 hours. Saturated sodium chloride is added for washing, and the mixture is dried to obtain a dicarboxyl silane monomer; Step 4: Disperse dicarboxyl silane monomer in water, heat the oil bath to 75-85°C, add acrylic acid and sodium methacrylic acid with stirring, use ammonium persulfate as initiator, keep warm for 2-3 hours, cool naturally after the reaction, then add NaOH solution to adjust the pH to 6-7 to obtain a modified water reducer.
2. The process for preparing dry-mixed high-strength fine stone concrete according to claim 1, characterized in that: The amount of each component, by weight, is 10-20 parts of mineral powder, 10-20 parts of silica fume, 10-20 parts of fly ash, 2-4 parts of modified water reducing agent, 0.5-1 part of defoaming agent, 0.2-0.3 part of expansion agent, 5-10 parts of early strength agent, 460-500 parts of Portland cement, 250-300 parts of fine stone, and 150-180 parts of sand.
3. The process for preparing dry-mixed high-strength fine stone concrete according to claim 1, characterized in that: The fine stone is granite with a particle size of 5 to 12 mm; the sand particle size is 0 to 4.7 mm; the mineral powder particle size is 300 to 400 mesh; the silica fume particle size is 350 to 400 mesh; and the fly ash particle size is 200 to 300 mesh.
4. The process for preparing dry-mixed high-strength fine stone concrete according to claim 1, characterized in that: In step 1, the molecular weight of methyl allyl polyoxyethylene ether is 2400-3000.
5. The process for preparing dry-mixed high-strength fine-stone concrete according to claim 1, characterized in that: In step 1, the molar ratio of 3,4-dihydroxyphenylacetic acid to methyl allyl polyoxyethylene ether is (2.5-3):
1.
6. The process for preparing dry-mixed high-strength fine-stone concrete according to claim 1, characterized in that: In step 2, the molar ratio of undecylenic acid to chlorodimethylsilane is 1:
1.
7. The process for preparing dry-mixed high-strength fine-stone concrete according to claim 1, characterized in that: In step 3, the esterification intermediate and the chlorine-containing carboxyl silane monomer are mixed in a molar ratio of phenolic hydroxyl group to chlorine group of 1:
1.
8. The process for preparing dry-mixed high-strength fine-stone concrete according to claim 1, characterized in that: In step 4, the weight ratio of dicarboxyl silane monomer, acrylic acid and sodium methacrylic acid sulfonate is (2-2.4):(18-20):
1.
9. Dry-mixed high-strength fine-stone concrete prepared by the preparation process according to any one of claims 1 to 8.
Citation Information
Patent Citations
Self-compacting C120 premixed dry concrete and preparation method thereof
CN112209683A